Killer Cell Immunoglobulin-like Receptors and their Ligands - F Shahsavar (Majallah-i Dānishgāh-i ̒Ulūm-i Pizishkī-i Qum, 2012)
The Natural killer (NK) cells are a subset of lymphocytes comprising around 10% of total lymphocytes in peripheral blood. Due to their role in the innate response, NK cells provide a ‘first line of defense’ against infectious agents and cancer and are also thought to play a role in autoimmunity. The killer cell immunoglobulin-like receptors (KIR) are regulatory surface molecules, found on NK cells and on a subset of T lymphocytes. The genes for KIR are present on chromosome 19 in the leukocyte receptor complex and show a major difference for both the type and number of KIR genes present among different ethnic groups. They have been divided into two groups of 2D or 3D, depending on the number of external immunoglobulin domains. The presence of a long cytoplasmic tail with two immune tyrosine-based inhibitory motifs (ITIM) allows the transduction of inhibitory signals and characterizes the inhibitory KIRs (2DL and 3DL), whereas the presence of short cytoplasmic tails corresponds to the activating KIR receptors (2DS and 3DS). These polymorphic receptors interact with specific motifs on human leukocyte antigen (HLA) class I molecules, modulate NK cytolytic activity. Some KIRs are known to interact with HLA-C molecules of target cells, HLA-Bw4 molecules and HLA-A3/11. For some KIRs the corresponding ligands are still unknown.